Effect of accelerometer-based feedback on physical activity in hospitalized patients with ischemic stroke: a randomized controlled trial. (August 2018) - Kanai, Masashi; Izawa, Kazuhiro P; Kobayashi, Miki; Onishi, Akira; Kubo, Hiroki; Nozoe, Masafumi; Mase, Kyoshi; Shimada, Shinichi
Objective: To evaluate the effect of accelerometer-based feedback on physical activity in hospitalized patients with ischemic stroke. Design: Randomized controlled trial. Setting: Acute care hospital. Subjects: A total of 55 patients with ischemic stroke who could walk without assistance were randomly assigned to the intervention group ( n  = 27) or the control group ( n  = 28). Interventions: At the baseline measurement, patients did not receive accelerometer-based feedback. At follow-up, a physical therapist provided instruction on accelerometer-based feedback, discussed physical activity targets and encouraged the patients to walk more until discharge. Main measures: The average daily number of steps taken was used as the index of daily hospitalized physical activity. Results: The study sample consisted of 48 patients, of whom 23 patients comprised the intervention group and 25 patients comprised the control group. Although there were no significant differences in physical activity values between the two groups at the baseline measurement, the values in the intervention group at follow-up were significantly higher than those in the control group (5180.5 ± 2314.9 vs. 3113.6 ± 1150.9 steps/day, P  = 0.0003). The effect size of physical activity values (Cohen's d  = 1.15) at follow-up was large between the two groups. Conclusion: Exercise training combined with accelerometer-based feedback effectively increased physical activity in hospitalized patients with ischemic stroke.